Giardia lamblia risk factors and burden in children with acute gastroenteritis in a Nicaraguan birth cohort. - Lester Gutiérrez; Nadja A Vielot; Roberto Herrera; Yaoska Reyes; Christian Toval-Ruíz; Patricia Blandón; Rebecca J Rubinstein; Javier Mora; Luther A Bartelt; Filemón Bucardo; Sylvia Becker-Dreps; Samuel Vilchez (PLoS Neglected Tropical Diseases)
Background Giardia lamblia is an intestinal protozoan estimated to cause ~200 million symptomatic infections annually, mainly in children in low- and middle-income countries associated with intestinal damage, increased permeability, and malabsorption. Methods and results We describe here the epidemiology, incidence, clinical characteristics, and risk factors of acute gastroenteritis episodes (AGE) with G. lamblia detection (GAGE) using a birth cohort of 443 Nicaraguan children followed weekly until 36 months of life. From June 2017 to July 2021, 1385 AGE samples were tested by qPCR. G. lamblia was detected in 104 (7.5%) of AGE episodes. In all, 69 (15.6%) children experienced at least one GAGE episode, and 25 of them (36.2%) experienced more than one episode. The incidence rate of the first episode of GAGE was 6.8/100 child-years (95% CI, 4.5-9.1). During GAGE, bloody stools, vomiting, and fever were uncommon, and children were less likely to be treated at a primary care clinic, suggesting that GAGE is typically mild and most cases did not receive medical attention, which could facilitate higher parasite loads with increased possibilities of establishing chronic carriage. GAGE was more common in children 12-24 months of age (13.9/100 child-years [95% CI, 10.7-17.1]) as compared to other age groups. In our birth-cohort, children living in a home with an indoor toilet (aHR, 0.52 [95%CI, 0.29-0.92]), and being breastfed in the first year of life (aHR: 0.10 [95%IC, 0.02, 0.57]) had a lower incidence of GAGE. In contrast, being breastfed for ≤ 6 months was associated with a higher incidence if the children were living in houses without indoor toilets and earthen floors (HR, 7.79 [95% CI, 2.07, 29.3]). Conclusion Taken together, GAGE is more frequent under poor household conditions. However, breastfeeding significantly reduces the incidence of GAGE in those children.